(untitled) (Mongolian Journal of Agricultural Sciences, 2021)
Most endophytes have beneficial properties for host plants, and some endophytic fungi are relatively harmless to plants, but some endophytic fungi can harm for animals. Thus, based on the study of edible plant of animals, we isolated from 2017 and 2018 years 71 pure cultures of endophytic fungi from the roots, stems and leaves of 6 plant species, such as Artemisia Frigida, Allium Bidentatum, Artenisia Adamsii, Kochia Prostrarta, Stipa Krylovii, Carex Duriuscula,. Based on the results we isolate seventy-one fungal strains from plant organs.The fungal strains identified based on their morphological characteristics such as Alternaria (16), Aspergillus (21), Fusarium (23), Pennicilium (6), Phoma (2), Trihoderma harzianum (2), Pestalotiopsis sp (1).Three classes, Dothiodeomycetes, Eurotiomycetes and Sordariomycetes have been identified in the DNA phylogenetic tree of the genomes of most edible plants of animal. According to the Statistical analysis of DCA process, Penicillium and Fusarium were found in 2017, and Aspegillus and Phoma were found in 2018. These differences suggest that different environmental parameters such as precipitation, temperature, humidity or seasonality play an important role in the distribution of endophytes. Бэлчээрийн зарим ургамлын эндофит мөөгөнцрийн судалгаа Ихэнх эндофитууд нь эзэн ургамалдаа ашигтай шинж чанар үзүүлдэг ба цөөхөн хэдэн эндофит мөөгөнцөр ургамлдаа өвчин үүсгэгч гэх үзүүлэх сөрөг нөлөө нь харьцангүй бага боловч мал гэмтээдэг болохыг тогтоосон байдаг. Иймд бид ургамлын идэмжийн судалгаанд тулгуурлан улирал тус бүрт мал сонгон идэж буй шивээт Хялгана, шүдлэг Сонгино, дэлхээ Тогторгоно, ширэг Улалж, агь Шарилж, адамсийн Шарилж зэрэг 6 зүйл ургамлын үндэс, иш, навчнаас эндофит мөөгөнцрийн 71 цэвэр өсгөвөр ялгасан. Ургамлын эрхтэн тус бүрээс цэвэр өсгөврийн төрлийн хамаарлыг морфологи шинж чанараар тодорхойлоход 7 төрөлд хамаарагдав. Үүнд: Ихэнх ургамлын өсгөвөрөөр Alternaria (16), Aspergillus (21), Fusarium (23), Pennicilium (6), Phoma (2), Trihoderma harzianum (2), Pestalotiopsis sp (1). Мал голлон иддэг ургамлын геномын ДНХ-н филогенетикийн мод хийхэд Dothiodeomycetes, Eurotiomycetes, Sordariomycetes гэсэн гурван анги илэрсэн. Статистик боловсруулалтын төсөөний процетоор (DCA) тодорхойлход Penicillium, Fusarium мөөгөнцөр 2017 онд илэрч байсан бол, 2018 онд Aspegillus, Phoma төрлийн мөөгөнцөр илэрч байна. Эдгээр ялгаа нь эндофитын тархалтад хур тунадас, агаарын температур, чийгшил эсвэл улирлын байдал зэрэг орчны янз бүрийн параметрүүд чухал үүрэг гүйцэтгэдэг болохыг харуулж байна. Түлхүүр үг: Мөөгөнцөр, эндофит, цэвэр өсгөвөр, молекул биологи